Reconstruction of the Teaching Module for Diversified Learning to Write Poetry with the Assistance of Image Media in the Independent Curriculum for Class VIII Students - Nilna Zakkiya 'Azmi; Mukh Doyin; Wagiran Wagiran (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was motivated by several problems identified in the teaching modules used in learning, including lack of interest, material that was difficult for students to understand, completeness of learning material, and module errors. This research aims to describe errors and describe the reconstruction of the teaching module for learning to write poetry in the independent curriculum for class VIII SMP students. This research uses an evaluative approach to evaluate teaching modules that have been prepared by teachers. The results of this research are that the reconstructed teaching module produces a module that is complete, effective, diversified and involves various appropriate systematic steps. Because there is an adjustment of learning outcomes to the flow of structured learning objectives including the development of competencies that students must master. The reconstructed module also contains three assessments, namely diagnostic, formative and summative. Learning media in the form of images is added to the reconstructed module to foster imagination. Various teaching modules can be used to improve the quality of poetry learning at the national level. With an innovative approach, Indonesian language and literature education becomes more interesting and effective. This contributes to the development of more competent and creative human resources. When students have good critical and creative thinking skills, they will be better prepared to face everyday challenges and make positive contributions to society.